All around rotation fault specimen holder - Yang Pu; Liu Xue; Hou Xiaoli; Huang Sheng; Yan Yonghao; Chen Rong; Wang Gang; Liu Chao; Ma Jinlong; Peng Guowen; Wang Dengke; Zhang Shaolei; et al. (2016)
The utility model belongs to an all around rotation fault specimen holder, including the base, the both sides of base are equipped with left stand and right stand respectively, are equipped with the crossbeam between the top of left stand and the top of right stand, the top of crossbeam is equipped with the roof, be equipped with the rotatable display?device of a plurality of between left side stand and the right stand, have simple structure, reasonable in design, can the human section morphological structure of three -dimensional show and relation each other and change rule, reinforcing medical science fan or the student's of medical college interest?in?learning, make this subject can obtain the advantage of effectively popularizing and promoting. 本实用新型属于种全方位旋转断层标本架；包括基座，基座的两侧分别设有左立柱和右立柱，左立柱的顶部和右立柱的顶部之间设有横梁，所述横梁的顶部设有顶板，所述左立柱和右立柱之间设有若干个可旋转展示装置；具有结构简单、设计合理、能够立体展示人体断面形态结构和相互之间的关系以及变化规律、增强医学爱好者或医学院学生的学习兴趣、使该学科能够得到有效普及和推广的优点。